2018
DOI: 10.1097/mao.0000000000001821
|View full text |Cite
|
Sign up to set email alerts
|

The Sound of a Cochlear Implant Investigated in Patients With Single-Sided Deafness and a Cochlear Implant

Abstract: We obtained a fairly good impression of what a CI can sound like for SSD patients. This may help to better inform and educate patients and family members about the sound of a CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Two studies recently conducted similar investigations in SSD subjects using different procedures (Dorman et al., 2017; Peters et al., 2018). Peters et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies recently conducted similar investigations in SSD subjects using different procedures (Dorman et al., 2017; Peters et al., 2018). Peters et al.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, CIs are simulated acoustically using channel vocoders, most often with a number of sinusoidal or noise-band carriers that emulate the electrical pulse trains delivered by the implanted electrodes (Bas¸kent & Shannon, 2004;Dudley, 1939;Rosen, Faulkner, & Wilkinson, 1999). Recently, it has been reported that the sound quality of these vocoders differs from the sound of a CI, as evaluated in SSD-CI subjects (Dorman, Natale, Butts, Zeitler, & Carlson, 2017;Peters et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the previously described experiment with speakers of Polish, mean similarity scores for noise and sine vocoders were between 2.0 and 3.0. Peters et al (2018) studied 10 SSD-CI patients fit with Cochlear Corporation CIs (type 422 with CP 910 or 920 processors) using noise and sine vocoders as input to the NH ear.Two of the three vocoders differed in configuration from those used in Dorman et al (2017). On a 1 to 10 scale, the average score for similarity between the vocoders and the CI was 6.8 for speech stimuli and 6.3 for music stimuli.…”
Section: Vocoders As An Acoustic Model Of the Sound Quality Of A CImentioning
confidence: 99%
“…CI performance appears to have reached a plateau in the last 30 years and despite an increase in scientific publications [2], a substantial number of challenges await future research. For example, a CI user's individual gradient of improvement is still hard to predict [3], disappointing outcomes remain hard to explain [4], speech perception in difficult listening situations remains extremely challenging for most CI users [5], and the quality of sound generated by CI stimulation is often considered unnatural and robotic despite decades of CI development [4,6].…”
Section: Introductionmentioning
confidence: 99%